Assessment of Dietary Intake, Body Composition and Sports Nutrition Knowledge of NCAA Division I Female Collegiate Volleyball Players. (29th May 2020) - Danh, Jessica; Nucci, Anita; Doyle, J Andrew; Feresin, Rafaela
Abstract: Objectives: To assess nutritional intake, body composition and sports nutrition knowledge of NCAA Division I female volleyball players. Methods: Nutritional intake was assessed using three-day food records. Daily average energy, carbohydrate, protein, fat, and specific vitamins and minerals intakes were analyzed using Food Processor 11.1. These values were compared to the recommendations from the American College of Sports Medicine (ACSM). Sports nutrition knowledge was assessed using an 87-question validated nutrition for sports knowledge questionnaire (NSKQ). Athletes were also asked to state their sources for nutrition knowledge. Body composition was assessed using bioelectrical impedance analysis. Descriptive data (mean ± SD) and Pearson correlation coefficients (r) were calculated using SPSS 26.0 with significance set at P ≤ 0.05. Results: Fourteen female volleyball players (age: 19.6 ± 1.3 y, height: 174.9 ± 8.2 cm, weight: 73.2 ± 8.5 kg, BMI: 24.1 ± 2.5 kg/m 2 ; body fat: 25.2 ± 3.4%) completed the study. Athletes' mean energy intake was 24.7 ± 6.4 kcal/kg BW/day, while carbohydrate, protein and fat intake were 2.9 ± 0.92, 1.3 ± 0.44, and 0.88 ± 0.28 g/kg BW/day, respectively. Vitamin D intake was 137.1 ± 90.7 IU/day and calcium intake was 673.4 ± 352.5 mg/day. Energy and carbohydrate intake were lower than the ACSM recommendations (37–41 kcal/kg BW/day and 6–10 g/kg BW/day, respectively) while fat intake was higher. Protein intake fell within the recommended ranges (1.2–1.7 g/kg BW/day). Additionally, vitamin D and calcium were lower than the recommendations. The average NSKQ score was 45.4 ± 9.6% and was positively associated with weight ( r = .738, P = 0.003) and vitamin D intake ( r = .587, P = 0.027). Weight management score (51.8 ± 15.4%) was positively associated with weight ( r = .676, P = 0.008). Four athletes included a registered dietitian nutritionist (RDN) as a source of nutrition information. In contrast, twelve athletes listed athletic trainers as a source. Conclusions: The average NSKQ score suggests that NCAA Division I female volleyball players lack adequate sports nutrition knowledge which may be associated with inadequate energy and nutrient intakes. Athletes may benefit from nutrition education and counseling for improved performance and health from RDNs. Funding Sources: There are no funding sources.